Analysis of the Rights of Persons with Disabilities Viewed from the Perspective of Human Rights for Workers - Tsabita Farras Azzahra (Yayasan Mentari Madani, 2023)
This study uses a Human Rights approach to investigate the rights of persons with disabilities in the work environment. This study thoroughly examines legal protections and employment practices involving persons with disabilities. This study evaluates the extent to which the rights of workers with disabilities are respected, protected, and fulfilled in the workplace using human rights frameworks. The analysis shows that despite progress in raising awareness about the importance of equity and inclusion in the workplace, there are still many challenges that need to be addressed. People with disabilities face many problems, including discrimination and inaccessibility to employment opportunities. In addition, the study identifies best practices and policies that have been shown to improve the quality of life of employees with disabilities. The implication of this research is the need for labor policy reforms that are more inclusive and based on human rights principles. Increased accessibility, elimination of discrimination, and empowerment through training and education are key steps to create a fair and equal working environment for all workers, including persons with disabilities. This research increases understanding of human rights protections in the world of work and provides a basis for policy changes that help the lives and careers of workers with disabilities